Religion, war, and ethics : a sourcebook of textual traditions - Reichberg, Gregory M.; Syse, Henrik; Hartwell, Nicole M. (New York : Cambridge University Press, 2014)
Religion, War, and Ethics is a collection of primary sources from the world's major religions on the ethics of war. Each chapter brings together annotated texts - scriptural, theological, ethical, and legal - from a variety of historical periods that reflect each tradition's response to perennial questions about the nature of war: when, if ever, is recourse to arms morally justifiable? What moral constraints should apply to military conduct? Can a lasting earthly peace be achieved? Are there sacred reasons for waging war, and special rewards for those who do the fighting? The religions covered include Sunni and Shiite Islam; Judaism; Roman Catholic, Eastern Orthodox, and Protestant Christianity; Theravada Buddhism; East Asian religious traditions (Confucianism, Shinto, Japanese and Korean Buddhism); Hinduism; and Sikhism. Each section is compiled by a specialist, recognized within his or her respective religious tradition, who has also written a commentary on the historical and textual context of the passages selected. -- Provided by publisher.
1. Judaism / Adam Afterman and Gedaliah Afterman -- 2. Catholic Christianity / Gregory M. Reichberg and Robert Araujo, S. J. -- 3. Eastern Orthodox Christianity / Yuri Stoyanov -- 4. Protestant Christianity / Valerie Ona Morkevicius -- 5. Sunni Islam / Nesrine Badawi and John Kelsay -- 6. Shi{u2829}te Islam / Mohammad Faghfoory -- 7. Hinduism / Kaushik Roy -- 8. The Buddhist traditions of South and Southeast Asia / Mahinda Deegalle -- 9. Chinese and Korean religious traditions / Vladimir Tikhonov -- 10. Religious traditions of Japan / Soho Machida -- 11. Sikh tradition / Torkel Brekke.
Includes bibliographical references and index.
Keywords: War -- Religious aspects; War -- Moral and ethical aspects; Just war doctrine